2020
DOI: 10.3390/antiox9121226
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid as a Tool to Limit the Diabetes Burden: Updated Evidence

Abstract: Oxidative stress contributes not only to the pathogenesis of type 2 diabetes (T2D) but also to diabetic vascular complications. It follows that antioxidants might contribute to limiting the diabetes burden. In this review we focus on ellagic acid (EA), a compound that can be obtained upon intestinal hydrolysis of dietary ellagitannins, a family of polyphenols naturally found in several fruits and seeds. There is increasing research on cardiometabolic effects of ellagitannins, EA, and urolithins (EA metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 134 publications
(251 reference statements)
0
30
0
Order By: Relevance
“…This is in line with previous studies on G. urbanum extracts ( Owczarek et al, 2015 ; Granica et al, 2016 ; Neshati et al, 2018 ; Al-Snafi, 2019 ). In particular, ellagic acid and its derivatives have been suggested to be very promising agents against DM and diabetic complications as recently summarized ( Amor et al, 2020 ). Some effects reported herein are of great interest in the context of our study: First, a α-glucosidase inhibition by ellagic acid-rich plant extracts is described which is far more effective than the inhibition of α-amylase ( Kam et al, 2013 ; Yin et al, 2014 ; Bellesia et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies on G. urbanum extracts ( Owczarek et al, 2015 ; Granica et al, 2016 ; Neshati et al, 2018 ; Al-Snafi, 2019 ). In particular, ellagic acid and its derivatives have been suggested to be very promising agents against DM and diabetic complications as recently summarized ( Amor et al, 2020 ). Some effects reported herein are of great interest in the context of our study: First, a α-glucosidase inhibition by ellagic acid-rich plant extracts is described which is far more effective than the inhibition of α-amylase ( Kam et al, 2013 ; Yin et al, 2014 ; Bellesia et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In randomized controlled trial and murine models, EA exhibits a favorable performance to improve blood glucose and diabetes‐related complications (Amor & Gómez‐Guerrero, 2020; Ghadimi et al., 2021). In T2DM patients, blood sugar and hemoglobin A1c are significantly downregulated in response to EA administration (Ghadimi et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our results of CML inhibition by EA are correlated with the study in which EA inhibited the accumulation of CML in the diabetic kidney [ 61 ]. The antiglycation studies of EA suggested that EA could protect the proteins to some extent against the formation of AGEs induced by glycation as evident by the progressive decrease in AGEs with increasing EA concentration [ 51 , 62 ].…”
Section: Resultsmentioning
confidence: 99%